2017
DOI: 10.1002/cbic.201700051
|View full text |Cite
|
Sign up to set email alerts
|

Chromate Binding and Removal by the Molybdate‐Binding Protein ModA

Abstract: Effective and cheap methods and techniques for the safe removal of hexavalent chromate from the environment are in increasingly high demand. High concentrations of hexavalent chromate have been shown to have numerous harmful effects on human biology. We show that the E. coli molybdate-binding protein ModA is a genetically encoded tool capable of removing chromate from aqueous solutions. Although previously reported to not bind chromate, we show that ModA binds chromate tightly and is capable of removing chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…Contradictory information is available on the binding of chromate to the E. coli ModA tungstate/molybdate binding protein. Whereas Rech et al found that it failed to bind even when tested at 2 mM [76], another study reported a chromate K D of approximately 100 nM [80]. Our data are thus in agreement with the latter study indicating that chromate is recognized by ModA in addition to molybdate and tungstate.…”
Section: Resultssupporting
confidence: 91%
“…Contradictory information is available on the binding of chromate to the E. coli ModA tungstate/molybdate binding protein. Whereas Rech et al found that it failed to bind even when tested at 2 mM [76], another study reported a chromate K D of approximately 100 nM [80]. Our data are thus in agreement with the latter study indicating that chromate is recognized by ModA in addition to molybdate and tungstate.…”
Section: Resultssupporting
confidence: 91%
“…In addition, sericin has both hydrophilic and hydrophobic as well as positively and negatively charged residues, which may confer on it exceptional binding capacities for heavy metals and other pollutants via noncovalent interactions. Similarly, Karpus et al recently showed the specic binding of Cr(VI) ions by the molybdate-binding protein ModA, 34 and Kwak et al recently showed Cr(VI) removal with sericin beads. 35 Hence, the incorporation of proteins into composites with adsorbent materials might be a viable strategy to improve the adsorption capacities of the adsorbent materials, as well as create an insoluble adsorbent from two materials that are soluble in various aqueous media.…”
Section: Introductionmentioning
confidence: 91%
“…For CrO, P. aeruginosa ModA had a K d value of 927.0 ± 87.7 nM, approximately 900-fold lower than MoO and WO ( Figure 1C ; Table 2 ). Thus, the relative affinity of P. aeruginosa PAO1 ModA for CrO is more similar to Bacillus strain EB106-08-02-XG196 ModA ( K d = 1.56 ± 0.5 μM; ~750-fold difference in affinity for CrO vs. MoO; Ge et al, 2020 ), than E. coli ( K d = 68–162 nM; ~2–4 fold difference in affinity for CrO vs. MoO; Karpus et al, 2017 ). Collectively, these data show that P. aeruginosa ModA has the capacity to interact with the oxyanions of group 6 metals and, notably, with greater affinity for MoO and WO than reported for orthologous ModA SBPs to date.…”
Section: Resultsmentioning
confidence: 91%
“…The result was a depletion in cellular Mo, with concomitant impacts on nitrate reductase activity and inhibition of anaerobic growth in WO-supplemented media ( Pederick et al, 2014 ). Recently, E. coli ModA was shown to also interact with chromate (CrO 4 2− ; henceforth CrO), the oxyanion form of the first group 6 element chromium (Cr), with a modest difference in relative affinity ( K d = ~68–162 nM) to MoO ( Karpus et al, 2017 ). Industrial use of chromium is widespread due to its favorable properties in the production of metal alloys, pigments, textile dyes, and applications in tanneries.…”
Section: Introductionmentioning
confidence: 99%